The Influence Of Personal And Work Environment Characteristics On Staff Engagement In Informal Learning Activities At Private Universities In The Sultanate Of Oman - Al-Araimi, Mubarak Ali Khamis (2018)
The objective of this study was to investigate the influence of personal and work environment factors on staff engagement in the informal learning at Omani private universities. A mixed method approach has been used to collect data from four selected private universities. The quantitative part consisted of questionnaire developed in Arabic and English languages. The data was gathered from 281 respondents to measure the personal and work environment factors’ influence on the staff’s engagement in informal learning activities. An inferential statistics were used to determine the influential effects. The results revealed that there are influences of different demographic aspects on staff engagement in informal learning and that that work environment and personal characteristics also influenced the employees’ level of engagement.